1981
DOI: 10.1016/0041-008x(81)90119-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acrylamide treatment upon the dopamine receptor

Abstract: . (1981). Toxicol. Appl. Pharmacol. 58,[89][90][91][92][93][94][95][96][97][98][99]. The binding of tritiated spiroperidol to striatal membranes prepared from acrylamide-treated male 6-week-old rats and matched controls has been studied. This binding has highaffinity characteristics and is stereospecific and reversible. Equilibrium was attained within 15 min at 37°C. The extent of binding was much more pronounced in the striatum than in any other brain region and was not detectable within the cerebellum or spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Acrylamide at a high dose is known to increase the activity of monoamine oxidase and decrease that of acetylcholinesterase in the developing rats and increase the striatal dopamine receptors in adult rats (Agrawal et al, 1981a(Agrawal et al, , 1981bHusain et al, 1987). Opposite effects as reflected by a decrease in the activity of monoamine oxidase and striatal dopamine receptors in our study may probably be due to nutritional influ-LPD LPD+ACR…”
Section: Discussioncontrasting
confidence: 53%
“…Acrylamide at a high dose is known to increase the activity of monoamine oxidase and decrease that of acetylcholinesterase in the developing rats and increase the striatal dopamine receptors in adult rats (Agrawal et al, 1981a(Agrawal et al, , 1981bHusain et al, 1987). Opposite effects as reflected by a decrease in the activity of monoamine oxidase and striatal dopamine receptors in our study may probably be due to nutritional influ-LPD LPD+ACR…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, regional distribution studies of receptor density confirmed the selective nature of binding. The stereospecificity of the spiroperidol binding was demonstrated using D and L butaclamol as competing agents (Agrawal et al 1980;Bondy 1980). The brain regions used for membrane preparation were chosen as containing a relatively high proportion of the receptor species being assayed (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…These changes were in the opposite direction to those caused by dosing of adult rats. A tendency of a toxic agent to cause opposite receptor changes in the brain of gestationally or neonatally exposed animals relative to adult exposure has also been observed in the case of acrylamide (Agrawal, et al .. 1981. Agrawal and Squibb, 1980).…”
Section: Discussionmentioning
confidence: 89%